2011
DOI: 10.1021/es200790x
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Desorption of Phenanthrene on Carbon Nanotubes in Simulated Gastrointestinal Fluids

Abstract: Adsorption of phenanthrene on carbon nanotubes (CNTs) and bioaccessibility of adsorbed phenanthrene were studied in simulated gastrointestinal fluids. Adsorption of phenanthrene on CNTs was suppressed in pepsin (800 mg/L) solution (gastric) and bile salt (500 and 5000 mg/L) fluids (intestinal). In addition to competitive sorption, pepsin and high-concentration bile salt (5000 mg/L, above critical micelle concentration) solubilized phenanthrene (3 and 30 times of the water solubility, respectively), thus substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
98
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(106 citation statements)
references
References 40 publications
5
98
3
Order By: Relevance
“…we incorporate past and emerging flame retardants (FRs), modern pesticides and legacy pollutants where previous papers are restricted to one chemical class e.g. polycyclic aromatic hydrocarbons (PAHs), polybrominated diphenyl ethers (PBDEs), phthalate esters (PEs) and organochlorine pesticides (OCPs) (Cheng et al, 2013;Gron et al, 2007;Wang et al, 2011b;Yu et al, 2009).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…we incorporate past and emerging flame retardants (FRs), modern pesticides and legacy pollutants where previous papers are restricted to one chemical class e.g. polycyclic aromatic hydrocarbons (PAHs), polybrominated diphenyl ethers (PBDEs), phthalate esters (PEs) and organochlorine pesticides (OCPs) (Cheng et al, 2013;Gron et al, 2007;Wang et al, 2011b;Yu et al, 2009).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Despite widespread use of these adsorbents in Pb removal, adsorption still has major limitations due to its high cost and low selectivity (Wang et al, 2011a). In addition, release of nano-adsorbents into air, water and soil likely cause potential toxicity to organisms (Wang et al, 2011b). Therefore, there is an urgent need for developing an environmental-friendly and low-cost adsorbent, which may be applied to reduce Pb 2+ pollution in water or soil.…”
Section: Introductionmentioning
confidence: 99%
“…However, the interaction behavior of CIP with rGO/GO in the presence of Mont remains to be reported so far. Several recent studies have reported the adsorption and desorption behaviors of aflatoxin on smectite 18 , phenanthrene on carbon nanotubes 19 , and bisphenol A and 17 α-ethinylestradiol on marine sediment 20 in simulated gastrointestinal fluids. These organic contaminants released from adsorbents in simulated digestive fluids further produce bio-toxicity or threaten environment health.…”
Section: Introductionmentioning
confidence: 99%